1999
DOI: 10.1076/0929-7049(199912)05:04;1-r;ft242
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analyses of Schooling Effects on Executive Function in Young Children

Abstract: Developmental studies have demonstrated the utility of select executive function (EF) tasks for the early diagnosis of specific learning-related problems (e.g., Snow, 1998). However, previous data demonstrating schooling effects on EF measures suggests potential pitfalls in clinical interpretation. In the present study three common EF measures, (Wisconsin Card Sort, Thurstone Word Fluency, and a mazes task) in addition to a VIQ estimating task, were administered to a cross-section of 115 children aged 7 to 9. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…Although some studies have found beneficial effects of schooling on various aspects of executive functioning (e.g., Burrage et al, 2008;McCrea, Mueller, & Parrila, 1999;Roebers et al, 2011), the findings have been inconsistent (see Roebers et al, 2011), and the effect sizes have been small. Despite the fact that the 5-to-7 shift has been an important topic in developmental psychology research, the emerging field of developmental cognitive neuroscience has thus far been silent about it.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Although some studies have found beneficial effects of schooling on various aspects of executive functioning (e.g., Burrage et al, 2008;McCrea, Mueller, & Parrila, 1999;Roebers et al, 2011), the findings have been inconsistent (see Roebers et al, 2011), and the effect sizes have been small. Despite the fact that the 5-to-7 shift has been an important topic in developmental psychology research, the emerging field of developmental cognitive neuroscience has thus far been silent about it.…”
mentioning
confidence: 86%
“…It would additionally be interesting to test whether cumulative effects emerge across elementary school. Tentative support for a cumulative effect comes from a cross-sectional cutoff study that revealed a stronger effect of age at school entry on inhibitory control in older compared with younger children (McCrea et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because common academic tasks for school-age children often involve the abilities to focus and sustain attention, to shift attention from task to task, and to inhibit dominant emotional and behavioral tendencies (e.g., sitting still), it is likely that school education partly contributes to the overall age-related development in effortful control. Indeed, McCrea, Mueller, and Parrila (1999) found that formal schooling was associated with the development of executive function (e.g., verbal fluency and planning) in grades 1 to 4.…”
Section: The Development Of Effortful Controlmentioning
confidence: 99%
“…Mobility of thinking, deductive reasoning, perseverance, and abilities to form abstract notions and to change a series learned for another [6,7,10,24,25,28,32,42,[44][45][46][47][48][49] Number of errors, total number of attempts, percent perseverance, and number of failures in maintaining a series Trail Making Test (tracing a path set by numbers alone or in combination with letters) Speed of visual search, mental flexibility, strategy of passing, change of series, visuomotor function, and visual planning skills [7,25,26,42,47,50,51] Time of performance and number of errors at each of the two levels of the test; total time of performance of both levels…”
Section: Twenty Questionsmentioning
confidence: 99%
“…Target components of executive functions Test parameters used to evaluate executive functions Rey Complex Figure ( CFR ) Capability for planning and organizational skills [6,7,14,[23][24][25][26][27][28][29][30] Accuracy, retrieval, organizational skills, and analysis of the copying process (logical or random) Maze Tasks ( Porteus mazes ) Planning and foreseeing [7,14,25,31,32] Passing time and number of errors Tower of London ( TOL ) and Tower of Hanoi ( TOH ) Problem solving [6,7,10,26,27,[33][34][35][36][37][38][39] Number of tasks performed correctly, number of unsuccessful attempts, time of planning, and time of performing each task Associative series ( Fluency Tests ; Controlled Oral Word Association Test ( COWAT ): free, semantic, phological, and switching tests) Capability for abstraction and formation of concepts, cognitive mobility, initiation, and inhibition of a response. Means to estimate the readiness of association exphoria and capability for actualizing words according to preset rules [7, 10, 14, 24-26, 28, 36, 37, 40-42] Total number of words actualized as a result of three attempts, number of repeated words, and number of rule violations…”
Section: Testmentioning
confidence: 99%